Design and Build Online Job Vacancy Application in Labuhanbatu Regency - Santika, Linda; Dar, Muhammad Halmi; Nasution, Marnis (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Labuhanbatu is a regency in North Sumatra Province which is geographically located on the main route of the east coast of Sumatra. Due to its geographical location, this district has an increasing population. Employment problems in Labuhanbatu Regency which are estimated to be increasingly complex, not to mention driven by the increase in the Open Unemployment Rate (TPT) in Labuhanbatu Regency, encourage the local government to expand and develop employment opportunities. However, Labuhanbatu Regency does not yet have a job vacancy information system that can be accessed by job seekers and companies. Online job vacancy information is a solution in providing information that has a very significant impact in saving time and costs compared to job vacancies in print media. The online job vacancy portal has succeeded in filling the vacancy for job vacancies. This study aims to design and build an online job vacancy application in Labuhanbatu Regency. The system development method used is the waterfall model, while the programming language used is PHP and MySQL DBMS. After designing and implementing the system, it was found that the System Development Life Cycle (SDLC) method with the waterfall model could be applied to build an online job vacancy application in Labuhanbatu Regency. It is hoped that this online job vacancy application can make it easier for job seekers in Labuhanbatu to receive job vacancies information so that the unemployment rate in Labuhanbatu Regency can be suppressed.